(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This study demonstrates the primacy of the ancient Kyrgyz alphabet over other known writing systems based on archaeological, linguistic, and historical evidence. Comparative analysis confirms its earlier structural and phonetic development.